Vocal, gestural and locomotor responses of wild chimpanzees to familiar and unfamiliar intruders: a playback study - Herbinger, Ilka; Papworth, Sarah; Boesch, Christophe; Zuberbühler, Klaus (My University, 2009)
Wild chimpanzees can be dangerously violent against individuals that do not belong to their community, indicating a strong selection pressure on decision-making abilities in this context. The presence of a neighbouring male indicates a serious threat, although encountering an unfamiliar male is potentially even more dangerous because it indicates the arrival of a new group with whom the subjects have no previous history of interaction.We conducted playback experiments with members of three chimpanzee, Pan troglodytes verus, communities in the Taï National Park, Côte d’Ivoire, in which we simulated the unexpected presence of another chimpanzee. We tested subjects’ responses to pant hoots of familiar group members, neighbouring individuals and unfamiliar strangers. We found that neighbours and strangers elicited a wider range of gestural signals than familiar group members. Vocal responses were common in all conditions. Familiar group members mainly triggered pant hoot replies, whereas neighbour and stranger trials caused screams. Across conditions, males responded more strongly than females. Male party size had an effect on subjects’ vocal responses to strangers but not to neighbours, although neighbours were approached more closely. Our results show that chimpanzees are able to identify different classes of individuals by their pant hoot vocalizations, as judged by their differential responses to the calls of familiar group members, neighbours or strangers. The overall response patterns suggest that chimpanzees are aware of the different social consequences associated with encountering a neighbouring group or a group of strangers.
Keywords: Aggression; cooperation; intergroup conflict; Pan troglodytes verus; pant hoots; territoriality; violence; vocal recognition; West African chimpanzee; xenophobia